Isolation and Identification of Campylobacter spp. from Poultry and Poultry By-Products in Tunisia by Conventional Culture Method and Multiplex Real-Time PCR - Jribi, Hela; Sellami, Hanen; Mariam, Siala; Smaoui, Salma; Ghorbel, Asma; Hachicha, Salma; Benejat, Lucie; Messadi-Akrout, Feriel; Mégraud, Francis; Gdoura, Radhouane (Journal of food protection, 2017)
Thermophilic Campylobacter spp. are one of the primary causes of bacterial human diarrhea. The consumption of poultry meats, by-products, or both is suspected to be a major cause of human campylobacteriosis. The aims of this study were to determine the prevalence of thermophilic Campylobacter spp. in fresh poultry meat and poultry by-products by conventional culture methods and to confirm Campylobacter jejuni and Campylobacter coli isolates by using the multiplex PCR assay. Two hundred fifty fresh poultry samples were collected from a variety of supermarkets and slaughterhouses located in Sfax, Tunisia, including chicken (n =149) and turkey (n =101). The samples were analyzed using conventional microbiological examinations according to the 2006 International Organization for Standardization method (ISO 10272-1) for Campylobacter spp. Concurrently, a real-time PCR was used for identification of C. jejuni and C. coli . Of the 250 samples of poultry meat and poultry by-products, 25.6% (n = 64) were contaminated with Campylobacter spp. The highest prevalence of Campylobacter spp. was found in chicken meat (26.8%) followed by turkey meat (23.7%). Among the different products, poultry breasts showed the highest contamination (36.6%) followed by poultry by-products (30%), poultry wings (28%) and poultry legs (26%) showed the lowest contamination, and no contamination was found on neck skin. Of the 64 thermophilic Campylobacter isolates, C. jejuni (59.7%) was the most frequently isolated species and 10.9% of the isolates were identified as C. coli . All of the 64 Campylobacter isolates identified by the conventional culture methods were further confirmed by PCR. The seasonal peak of Campylobacter spp. contamination was in the warm seasons (spring and summer). The study concluded that high proportions of poultry meat and poultry by-products marketed in Tunisia are contaminated by Campylobacter spp. Furthermore, to ensure food safety, poultry meats must be properly cooked before consuming.